Biosynthesis of gold nanoparticles by Penicillium rubens and catalytic detoxification of ochratoxin A and organic dye pollutants - Bhandari, Yogesh; Varma, Sanjana; Sawant, Amol; Beemagani, Sreelatha; Jaiswal, Neha; Chaudhari, Bhushan P.; Vamkudoth, Koteswara Rao (International Microbiology, 2023)
The environmental pollution caused by chemical dyes is a growing concern nowadays. Limitations of traditional methods opened the route for nanotechnology; owing to the versatile properties of nanomaterials, gold nanoparticles (AuNPs) became a potential strategy for different applications. In the present study, biosynthesis of gold nanoparticles (BioAuNPs) was carried out by reacting chloroauric acid (HAuCl4) with cell-free filtrate of Penicillium rubens sp. nov. NCIM 1937. The AuNPs were then characterized by UV-visible spectroscopy, HR-TEM, FTIR, and DLS analysis to further examine their efficacious biosynthesis and morphological properties including size, shape, and stability. The biogenic AuNPs are polydisperse in nature, with a mean size of 14.92 +/- 5 nm. These AuNPs exhibited promising antimicrobial activity against Escherichia coli NCIM-2065, Bacillus subtilis NCIM-2010, and Penicillium verrucosum MTCC 4935. In vitro quantitative HPLC results revealed that BioAuNPs significantly inhibited the biosynthesis of ochratoxin A (OTA). Microbial fuel cells (MFCs) are intriguing for power generation and wastewater treatment since they can directly transform chemical energy stored in organic matter to electricity by extracellular electron transfer (EET) via membrane proteins. AuNPs also showed excellent potential for dye degradation of organic pollutants, viz., methylene blue (MB), phenol red (PR), bromothymol blue (BTB), Congo red (CR), and 4-nitrophenol (4-NP). All dye removal efficiencies were estimated and fitted to pseudo-first-order processes using kinetic rate constants (Ka).The present study reveals a simple, original, and eco-friendly method for the synthesis of multifunctional biogenic AuNPs that could be effective in OTA detoxification in food products and organic pollutant removal during wastewater treatment for a sustainable environment.
Keywords: Catalytic organic dye degradation; gold nanoparticles; Ochratoxin A; Penicillium rubens; Penicillium verrucosum

Chloroperoxidase applications in chemical synthesis of industrial relevance - Bhandari, Yogesh; Sajwan, Hemlata; Pandita, Parul; Koteswara Rao, Vamkudoth (Biocatalysis and Biotransformation, 2023)
Biocatalysts can accelerate the catalysis of a chemical reaction that is difficult to synthesize with typical chemical methods. The global enzyme market size is predicted to expand at a CAGR of 6.5% from 2021 to 2028. Enzymatic reactions are highly chemo, regio, and stereoselective and produce various fine chemicals such as drugs, agrochemicals, and fragrance molecules. Peroxidases (PO) (EC 1.11.1.x) are a large class of enzymes that play an important role in various biological processes. Chloroperoxidase (CPO, EC 1.1.1.10) is a versatile fungal haem-thiolate protein that is useful in the asymmetric synthesis of chiral building blocks and has an important role in a number of biological processes. CPO's main biological role is chlorination, although it also catalyses haem PO, catalase (CAT), and reactions similar to cytochrome P450. However, CPO performs both oxidation and stereo-specific halogenation of chemical molecules. The haem and vanadium POs are produced by Caldariomyces fumago, and Curvularia inaequalis, respectively, and are capable of halogenating the flavanones, naringenin, and hesperetin, at C-6 and C-8 in the presence of either Cl- or Br-. In this review, we discussed the various applications of CPO including synthesis of epoxides, drugs, halogenation of thymol, nitriles, the Aza-Achmatowicz reaction, and biomedical applications such as cancer and biosensors. In light of these novel features, we have provided a detailed review of CPOs and their applications in various stereoselective chemical transformations of industrial relevance.
Keywords: active pharmaceutical ingredients; Biotransformation; Caldariomyces fumago; chemo; Chloroperoxidase; regio; stereoselectivity

Development of novel ssDNA aptamers for detection of receptor-binding domain of SARS-COV-2 - Auti, Amogh; Yadav, Pranay; Bodkhe, Rahul; Bhandari, Yogesh; Varma, Sanjana; Chaudhari, Bhushan; Rahi, Shraddha; Ghormade, Vandana; Vamkudoth, Koteswara Rao (ACS Omega, 2025)
The highly virulent and transmissible SARS-CoV-2 causes COVID-19 and poses a global public health threat. Herein cloned, expressed, and the molecular weight of the receptor-binding domain (RBD) of the SARS-CoV-2 gene encoding protein was confirmed by SDS-PAGE electrophoresis and Western blot analysis. The pivotal aim is to develop single-stranded DNA (ssDNA) aptamers for the rapid detection of SARS-COV-2 infections in humans. In this investigation, a library of nine novel ssDNA aptamers was developed by several rounds of systematic evolution of ligands by an exponential enrichment approach and assessed by an enzyme-linked aptamer assay for binding affinity against RBD antigen (Ag). An in vitro assay resulted in a varied colorimetric signal that depends on the nature of aptamer. Quantitative determination of AptRBD3, AptRBD6, and AptRBD8 aptamers exhibited excellent binding affinity against Ag in the range of 5-10 ng/mL. The putative AptRBD3, AptRBD6, and AptRBD8 aptamers were converted into peptide sequences and docked against RBD, exhibiting good binding energy of -6.8, -6.3, and -7.1 kcal/mol respectively, which were recorded. Furthermore, docking studies of ssDNA aptamers were performed using HDOCK web server to ascertain the binding mechanism and docking score perceived as -389.74, -404.28, and -390.37. Despite this, we engineered a high-affinity AptRBD3.3 aptamer that formed a single and bulged loop, which improved binding affinity, resulted in a docking score of -361.56, and exhibited sensitivity at 4 ng of Ag of SARS-CoV-2. Moreover, computational modeling of AptRBD3.3 revealed an intriguing significant binding affinity with the RBD mutant SARS-CoV-2 S-UK variant (PDB ID: 7EDG) with a docking score of -350.21. In conclusion, the AptRBD3.3 aptamer can be used for the development of lateral flow device and electrochemical sensors for rapid, low-cost, and accurate detection of COVID-19 infection in humans for point of care diagnostics.